Challenges and Strategies of Cooperatives in Implementing ISO 26000 for Sustainable Economic Development - Muhammad Rusli; Kurniawati Kurniawati; Maria Ariesta Utha (Jurnal Manajerial, 2023)
Background – Family is a key factor in creating quality resources to support successful development (Cabrera-Suarez, 2001). One of the family's responsibilities in improving the economy is to form a business group to generate additional income for the family (Morck, R & Young. B, 2003). The problem that is often faced by family businesses and small businesses is the lack of sources of capital and knowledge to run their businesses so that they can develop and expand their marketing. Luo, X., & Shen, J. (2009) stated that there is a need for a forum to improve the quality of human resources in small businesses. One of the most effective and efficient forums is the formation of cooperatives. Objective – To analyze and evaluate the challenges and strategies of savings and loan cooperatives in implementing ISO 26000 for sustainable economic development, so as to improve the economy of the surrounding community or certain areas. Design / methodology / approach – This study uses an approach to analyze the role of Savings and Loans Financial Institutions in good governance in terms of the implementation of ISO 26000 and the issues and strategies applied. The subject of this research is the Savings and Loans Financial Institution. The survey respondents interviewed the directors of financial institutions and operational managers and financial managers as well as stakeholders in savings and loan financial institutions. This study was analyzed using content analysis. Findings – With these challenges and strategies, it is hoped that Savings and Loans Financial Institutions can carry out sustainable economic development (SDGs) as in point 1 and point 8 and point 9 and point 17, namely: a) SDGs No. 1 concerning Poverty Alleviation: Encouraging economic activity in rural areas and regions to reduce poverty, b) SDGs No. 8 on Decent Work and Economic Growth: Encouraging participation among low-income families for decent work and growing the economy, c) SDGs No. 9 on Reducing Inequalities: Strengthening the social capital of the rural population to reduce inequality in the community, d) SDGs No 17 concerning Partnerships to Achieve Goals: Strengthen the social capital of rural residents for partnerships that can grow family businesses so that the goals of economic growth are achieved. Research implication – It is expected to be able to maintain several core courses that have been implemented properly, although not yet optimal, they should still be implemented in accordance with the vision and mission, culture and values of core competencies, SOP, Jobdisc, KPI and standardization in all parts of the HR line. Finance, marketing, operations and others pay attention to good governance to achieve good performance. Savings and loan institutions are expected to be able to create a good management system so that they can influence the results of savings and loan institutions to achieve goals and achieve goals. The existence of a savings and loan institution is expected to become a social (community) business that can provide social value to the community and overcome social problems, turning them into solutions through business. Limitations Of Research – This study only covers all the ISO 2600 standard topics related to organizational governance, human rights, labor practices, environment, fair practices, consumer issues and community participation and development in savings and loan institutions. And the extent to which the management of the Savings and Loans Institution for Sustainable Economic Growth (SDG) has implemented aspects of the ISO 26000 standard.